ANALISIS DESAIN PESAN DAN MATERI PEMBELAJARAN BAHASA ARAB DALAM BUKU AJAR DURUUS AL MUFRADAAT WA AL MUHAADATSAAT AL ‘ARABIYAH - Mukroji Mukroji (Institut Agama Islam Negeri Purwokerto, 2016)
STAIN Purwokerto has target of Arabic learning on campus, thestudents can talk and communicate with fluent Arabic and actively correct . This target would be difficult to achieve if not supported by the mastery of vocabulary and conversation. Therefore , the book